Policy Implementation Analysis: Exploration of George Edward III, Marilee S Grindle, and Mazmanian and Sabatier Theories in the Policy Analysis Triangle Framework - Mubarok, Syahrul; Zauhar, Soesilo; Setyowati, Endah; Suryadi, Suryadi (FIA UB, 2020)
Policy implementation is an equally important process of policy formulation in the context of achieving policy objectives. Although a policy has been well and neatly arranged, the purpose of the policy will never be achieved if the policy is not implemented properly. Policy research is a study of policies intended for the general interests of policies or implemented policies. There are several policy model implementation theories. Some of them are Edward's model, Grindle's model, Mazmanian and Sabatier's model. These policy implementation model has several advantages and disadvantages in its implementation. Using policy analysis triangle framework, these three implementation models can be made as an optimized policy implementation analysis method which has the advantages of the three models and meets the comprehensive and integrative aspects of an organization. The result presented in this study is a design of the policy implementation analysis method based on George Edward III, Marilee S Grindle, and Mazmanian & Sabatier policy implementation model.